Contemporary Syirkah Perspective of Hadith History of Abu Dawud Number 3,383 - Silvia Ifta Fauziyah; Itmamul Wafa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Syirkah is a form of company with the principles of business partnership and profit sharing which is completely different from the capitalist economic system. As time progresses, Contemporary Shirkah products emerge which, according to Al-Zuhaili, must remain based on classic Syirkah products. Apart from that, contemporary Shirkah products must be in accordance with the basic postulates of Islamic law, namely the Al-Qur'an and Hadith. This research focuses on explaining the suitability of contemporary Shirkah to the arguments of the hadith qudsi narrated by Abu Dawud No. 3,383. This type of research uses library research with a qualitative approach. Data were analyzed using descriptive-analytic methods. This research resulted in the conclusion that Contemporary Shirkah Products are in accordance with the argument of Hadith narrated by Abu Dawud No. 3,383 which has authentic status by fulfilling the three basic principle values ​​contained in the hadith, namely the values ​​of the principle of trust and non-betrayal, regardless of religion, and equality of rights and responsibilities according to the initial agreement.